Regulation of placental leptin expression by cyclic adenosine 5′-monophosphate involves cross talk between protein kinase A and mitogen-activated protein kinase signaling pathways - Maymó, J.L. (2010)
Leptin, a 16-kDa protein mainly produced by adipose tissue, has been involved in the control of energy balance through its hypothalamic receptor. However, pleiotropic effects of leptin have been identified in reproduction and pregnancy, particularly in placenta, where it was found to be expressed. In the current study, we examined the effect of cAMP in the regulation of leptin expression in trophoblastic cells. We found that dibutyryl cAMP [(Bu) 2cAMP], a cAMP analog, showed an inducing effect on endogenous leptin expression in BeWo and JEG-3 cell lines when analyzed by Western blot analysis and quantitative RT-PCR. Maximal effect was achieved at 100 μM. Leptin promoter activity was also stimulated, evaluated by transient transfection with a reporter plasmid construction. Similar results were obtained with human term placental explants, thus indicating physiological relevance. Because cAMP usually exerts its actions through activation of protein kinase A (PKA) signaling, this pathway was analyzed. We found that cAMP response element-binding protein (CREB) phosphorylation was significantly increased with (Bu)2cAMP treatment. Furthermore, cotransfection with the catalytic subunit of PKA and/or the transcription factor CREB caused a significant stimulation on leptin promoter activity. On the other hand, the cotransfection with a dominant negative mutant of the regulatory subunit of PKA inhibited leptin promoter activity. We determined that cAMP effect could be blocked by pharmacologic inhibition of PKA or adenylyl ciclase in BeWo cells and in human placental explants. Thereafter, we decided to investigate the involvement of the MAPK/ERK signaling pathway in the cAMP effect on leptin induction. We found that 50 μM PD98059, a MAPK kinase inhibitor, partially blocked leptin induction by cAMP, measured both by Western blot analysis and reporter transient transfection assay. Moreover, ERK 1/2 phosphorylation was significantly increased with (Bu)2cAMP treatment, and this effect was dose dependent. Finally, we observed that 50 μM PD98059 inhibited cAMP-dependent phosphorylation of CREB in placental explants. In summary, we provide some evidence suggesting that cAMP induces leptin expression in placental cells and that this effect seems to be mediated by a cross talk between PKA and MAPK signaling pathways. Copyright © 2010 by The Endocrine Society.